Words matter: how institutional disruption policies reinforce white power in higher education - Zanotto, Anton, author; Barone, Ryan, advisor; McKelfresh, David, advisor; Chesson, Craig, committee member; Opsal, Tara, committee member (Colorado State University. Libraries, 2023)
Student conduct exists as the intersection of student development theory, legal compliance, and institutional policies. While literature in the K-12 and criminal legal system shows the way that policy has a disproportionately negative impact on Black, Indigenous, and other People of Color, there are few studies that do similar work in higher education. Furthermore, research in student conduct largely focuses on student learning and conduct administrator practices and does not consider the policies at the root of our practice. This study explores the campus discourse about disruption at eight institutions of higher education and uses a theoretical framework that uniquely considers the various nuances of this work. By centering the policies and using a critical policy discourse analysis methodology, I enter the discussion about how to create liberatory policy that subsequently supports the practice of many student conduct administrators. The subsequent model offers a set of guiding principles for liberatory policy revision and development for the future.
Keywords: disruption; liberatory; student conduct; higher education; discourse analysis; policy